Activated carbon electrodes: Electrochemical oxidation coupled with desalination for wastewater treatment. (April 2015) - Duan, Feng; Li, Yuping; Cao, Hongbin; Wang, Yi; Crittenden, John C.; Zhang, Yi
Highlights: Simultaneous organics degradation and salt removal were realized. Salt and phenol removal efficiency were enhanced by bubbling O2 gas. Phenol degradation was related to the electrogenerated chlorine oxidants. Abstract: The wastewater usually contains low-concentration organic pollutants and some inorganic salts after biological treatment. In the present work, the possibility of simultaneous removal of them by combining electrochemical oxidation and electrosorption was investigated. Phenol and sodium chloride were chosen as representative of organic pollutants and inorganic salts and a pair of activated carbon plate electrodes were used as anode and cathode. Some important working conditions such as oxygen concentration, applied potential and temperature were evaluated to reach both efficient phenol removal and desalination. Under optimized 2.0 V of applied potential, 38 °C of temperature, and 500 mL min −1 of oxygen flow, over 90% of phenol, 60% of TOC and 20% of salinity were removed during 300 min of electrolysis time. Phenol was removed by both adsorption and electrochemical oxidation, which may proceed directly or indirectly by chlorine and hypochlorite oxidation. Chlorophenols were detected as degradation intermediates, but they were finally transformed to carboxylic acids. Desalination was possibly attributed to electrosorption of ions in the pores of activated carbon electrodes. The charging/regeneration cycling experiment showed good stability of the electrodes. This provides a new strategy for wastewater treatment and recycling.